Swine Wastewater Treatment Using Water Fern (Azolla microphylla) in Floating Aquatic Plant Wastewater Treatment System - กล่อมเจ๊ก พันธ์ทิพย์; หอมหวน วิภา; สุวรรณศรี ดำรงศักดิ์; พลฤทธิ์ นุชนันท์ (KKU Science Journal, 2015)
The purposes of this study were to evaluate of swine wastewater treatment and production of water fern in floating aquatic plant wastewater treatment system. Efficiency of the system with water fern (Azolla microphylla) for treating of 25 % dilution swine wastewater was examined. Pollutant removal efficiencies of the system at different plant harvest intervals (every 1, 2 and 3 week) were compared. The result showed that average removal efficiencies of the system for COD, BOD5 , TSS, TDS, TKN and TP in each week were (-125.0)-35.4, (-22.2)-60.0, (-502.9)-54.7, (-1.7)-13.7, (-79.5)-51.5 and (-429.5)-52.0 %, respectively. There were not significantly different between pollutant removal efficiencies of systems operated at various plant harvest intervals. Increasing of water fern yield in tested system was low comparing with yield from conventional culture system in suitable environment. For 6 weeks of operation, the highest net fresh water fern yield was found in the system operated at every week of harvest interval however it was similar to net fresh yield of water fern from the system operated at every 2 week of harvest interval.